(untitled) (Advances in Civil and Architectural Engineering, 2021)
This article describes the study of reinforced concrete span bending structures under conditions of high-level cyclic loading. Previous studies on the development of physical models of bending reinforced concrete element fatigue resistance, cyclic effect of lateral forces, and methods of calculation, are important and appropriate owing to certain features and the essential specificity of the mentioned loading type. These primarily include the nonlinearity of deformation, damage accumulation in the form of fatigue micro- and macro-cracks, and exhausting destruction of construction materials. In this paper, key expressions determining the endurance limits of concrete, longitudinal reinforcement, and anchoring longitudinal reinforcement, which contribute to endurance throughout the entire construction, are considered. Establishing a link between stresses in the elements and deformations in the element under conditions of cyclic loading action is of equal importance because of the presence of cyclic stress-induced creep deformation.